A selection model based on SWOT analysis for determining a suitable strategy of prefabrication implementation in rural areas. (October 2019) - Zhou, Jingyang; He, Pengwang; Qin, Yanjun; Ren, Dandan
Highlights: Twelve factors influencing prefabrication implementation in rural areas were identified. A strategy selection model integrating SWOT analysis and strategic vector method was designed. Four scenarios of strategies were presented and some useful implications were provided. A case study of Jinan city was conducted to demonstrate the applicability of this model. Abstract: The construction of rural residential buildings has a great impact on the achievement of sustainable countryside. It needs a cleaner construction method. This study argues that prefabrication should be adopted in rural areas, but different strategies should be designed based on the strengths, weaknesses, opportunities, and threats (SWOT). This issue has not been involved in previous studies. This paper aims to design a model for determining the suitable strategy of prefabrication implementation. Twelve factors affecting the prefabrication implementation were firstly identified for SWOT analysis, including prefabricated construction standards, ecological benefits, transportation capacity, and so on. A strategy selection model expressed by strategic vector (θ, ρ) was then designed, in which strategic azimuth (θ) determines the strategy type and intensity coefficient (ρ) determines the attitudes that should be taken to the selected strategy. Four types of strategies (aggressing, pioneering, reverse, and avoidant) and two development intensities (conservative and proactive) were summarized. The model was substantiated in a village of Jinan as a case. It was identified that aggressing strategy with conservative attitude is the optimal strategy to the current conditions in rural Jinan. The developed model can be adopted by other rural areas for devising their suitable prefabrication development strategies.